Modelos para estimar exigências nutricionais de aminoácidos e resposta à ingestão de metionina: sistema tradicional por fases x nutrição de precisão - Remus, Aline [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this dissertation is to support the first steps to develop a new method to estimate methionine nutritional requirements for the pigs fed individually. The first step of this dissertation was perform a meta-analysis in order to study the response of pigs fed with different types of methionine and to quantify the ideal ratio of methionine: lysine for piglets from the initial phase to termination. The database consisted of 41 papers. To determine the methionine: lysine ratios, 83% of papers in the database were excluded because they did not meet the pigs requirement for lysine. For analysis of methionine sources were used 21 papers from initial phase, and it had no difference (P <0.05) between L-methionine, DL-methionine and methionine hydroxy-analogue. The minimum methionine: lysine ratio found was 26% methionine inclusion in function of lysine requirement. In sequence was performed a simulation study using factorials models used in pig farming (Brazilian tables of nutritional requirements for pigs and poultry (BT) and the NRC 2012), in order to compare them with the model Automatic and intelligent Precision feeder (AIPF). Data from 36 pigs were used with initial body weight of 25 kg for a period of 28 days. Body weight, feed intake and average daily gain were standardized. It was concluded that the NRC and BT models were calibrated to estimate the maximum response requirements of the population, thus overestimate the average pig requirement in more than 13%. In addition, the requirement of using an average pig in the middle of the feeding phase to estimate the requirements of a population, is a practice which must be handled with care. This is due to the wide variation in nutritional requirements that exist between the pigs from the same population. Finally the AIPF and BT models were used in a trial. The pigs were arranged in a randomized design, 2x3 factorial randomized design: two feeding programs (individual daily ...

Objetivou-se através dessa dissertação embasar os primeiros passos para desenvolver uma nova maneira de estimar as exigências nutricionais de metionina para suínos alimentados individualmente. O primeiro passo foi uma meta-análise conduzida objetivando estudar a reposta de suínos alimentados com diferentes tipos de metionina, bem como quantificar a relação ideal de metionina: lisina para leitões da fase inicial a terminação. A base de dados foi composta por 41 artigos. Para determinação da relação metionina: lisina, 83% dos artigos da base forem excluídos pois não atendiam a exigência de lisina. Para análise de fontes de metionina foram utilizados 21 artigos para fase inicial não havendo diferença (P<0.05) entre L-metionina, DL-metionina e metionina hidroxi-análoga. A relação mínima de metionina: lisina encontrado foi de 26% de inclusão de metionina em função da exigência de lisina, uma relação menor que essa poderá representar perdas significativas no desempenho. Na sequencia foi realizado uma simulação com modelos fatoriais utilizados na suinocultura (Tabelas brasileiras de exigências nutricionais para suínos e aves (BT) e o NRC 2012), objetivando compara-los com o modelo do Automatic and inteligent Precision feeder (AIPF). Foram utilizados dados de 36 suínos com peso inicial de 25 kg, por um período de 28 dias. Peso corporal, consumo de ração e ganho médio foram estandardizados. Concluiu-se que os modelos NRC e BT foram calibrados para estimar as exigências de resposta máxima da população, assim, superestimam as necessidades do indivíduo médio em mais de 13%. Além disso, usar a exigência de um suíno ...
Keywords: Suino; Suino - Nutrição; Metionina; Lisina na nutrição animal; Aminoacidos na nutrição animal; Levantamentos nutricionais; Methionine